(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In order to provide access and links throughout Maharashtra, the Maharashtra State Road Transportation Corporation (MSRTC) was important. The financial performance of MSRTC in recent years has worsened markedly due to a number of issues, especially competition from the private sector. Passenger road transport has traditionally been mostly in the field of public transit in India. In 1950 Parliament adopted in India the Road Transport Corporation Act (today known as ’RTC Act’). This Act called for the nationalization of road transport services for passengers in Union countries. It is the foundation of State Road Transport Corporations (SRTCs). Section 18 of the RTC Act stipulates that the corporation shall have a general obligation to gradually use its powers in order to deliver or ensure, or develop a system of road transport services that is effective, appropriate, economic and adequately coordinated Further Article 22 of the Operate states that it acts on ’business principles.’ The Corporation shall act The Industrial Policy Decree of 1956, contained in Schedule B passenger carriage by the passenger road business, was in line with the RTC Act. With the group defined by a gradual government control, the industry was included in the hope that the States would take the lead in creating new ventures. In July 1948, when a department of the provincial authorities commenced operation with a flood of 36 buses on Poona - Ahmednagar and associated routs that were subsequently transferred to the statutory corporation, a process began in the State of Maharashtra.